2018
DOI: 10.1039/c7cy02048a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of strong bifunctional electrocatalytically active hybrid Cu–Cu2O nanoparticles in a carbon matrix

Abstract: Earth-abundant copper-based hybrid Cu–Cu2ONPs@C in the carbon matrix exhibited enhanced OER and HER catalytic activity compared to pure Cu2O and CuNPs@C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Recently, several groups have reported that the electrocatalytic performance of Cu 2 O‐based catalysts can be enhanced by the elaborate design of their microstructures, morphologies, and chemical compositions . For example, 3D Cu/Cu 2 O–CuO/rGO composites, a hybrid of Cu–Cu 2 O nanoparticles in a carbon matrix (Cu–Cu 2 ONPs/C), (RGOL/PPS/CNT+RGO)‐Cu 2 O film, and Ag@Cu 2 O/N‐RGO composites have been fabricated to lower the overpotential and improve the electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups have reported that the electrocatalytic performance of Cu 2 O‐based catalysts can be enhanced by the elaborate design of their microstructures, morphologies, and chemical compositions . For example, 3D Cu/Cu 2 O–CuO/rGO composites, a hybrid of Cu–Cu 2 O nanoparticles in a carbon matrix (Cu–Cu 2 ONPs/C), (RGOL/PPS/CNT+RGO)‐Cu 2 O film, and Ag@Cu 2 O/N‐RGO composites have been fabricated to lower the overpotential and improve the electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…1.25 mg cm −2 based on geometric surface area. Powder X‐ray diffraction (pXRD, Supporting Information, Figure S8) showed the presence of crystalline Cu 2 O, which is a known semiconductor with high electron mobility and has recently been reported as OER and HER catalyst . Scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDX) and transmission electron microscopy (TEM) showed a homogeneous deposition of spherical nanoparticles (diameter ≈200–600 nm) and high aspect‐ratio nanowires (diameter ≈50 nm, length >4 μm, Figure and Figure S6) on the macroporous support.…”
Section: Figurementioning
confidence: 84%
“…Thew ashed and dried samples (hereafter: Electrode 1)w ere examined by gravimetric studies which gave ac atalyst loading of ca. [23,[29][30][31][32][33] Scanning electron microscopy (SEM), energy dispersive X-ray spec-troscopy (EDX) and transmission electron microscopy (TEM) showed ah omogeneous deposition of spherical nanoparticles (diameter % 200-600 nm) and high aspectratio nanowires (diameter % 50 nm, length > 4 mm, Figure 2 and Figure S6) on the macroporous support. Powder Xray diffraction (pXRD,S upporting Information, Figure S8) showed the presence of crystalline Cu 2 O, which is ak nown semiconductor with high electron mobility [28] and has recently been reported as OER and HER catalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Cu 2‐x Se has an efficient HER activity in an acidic electrolyte, but it is necessary to improve its HER performance in pH‐universal electrolytes for commercialization. Recently published research works suggest that manipulation of the metal oxide surface is an useful direction for enhancing their HER performance because oxides such as NiO, Co 3 O 4 , Cu 2 O, CeO 2 , Mn 3 O 4 , and TiO 2 can participate in the reaction as water splitting promoters for HER. Although the use of Cu 2 O itself as a HER electrocatalyst is restrained due to its high overpotential and low current densities, the combination of Cu 2 Se with water dissociation promoters (Cu 2 O) by engineering the anion contents is expected to not only boost the HER kinetic but also optimize the free energy for hydrogen adsorption to achieve a high HER performance.…”
Section: Introductionmentioning
confidence: 99%